2016
DOI: 10.1016/j.bjm.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ultrasound on survival and growth of Escherichia coli in cactus pear juice during storage

Abstract: The aim of this study was to investigate the effectiveness of ultrasound as a conservation method for the inactivation of Escherichia coli inoculated into cactus pear juices (green and purple). Total soluble solids, pH, titratable acidity, and the kinetics of E. coli in cactus pear juices treated by ultrasound (60%, 70%, 80% and 90% amplitude levels for 1, 3 and 5 min) were evaluated over 5 days. Total inactivation was observed in both fruit juices after 5 min of ultrasound treatment at most amplitude levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…Meanwhile, it was previously established also that, for the same ultrasonic power delivered, the inactivation rate was somewhat superior at 500 kHz than at 20 kHz frequency during sonication of bacterial suspension. The efficacy of US inactivation of E. coli and most microorganisms depends on the frequency and treatment time (Cruz‐cansino et al, ). It is suggested that prolonging US treatment time could decrease to a larger extent the microbial load of sonicated samples (Zou & Jiang, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, it was previously established also that, for the same ultrasonic power delivered, the inactivation rate was somewhat superior at 500 kHz than at 20 kHz frequency during sonication of bacterial suspension. The efficacy of US inactivation of E. coli and most microorganisms depends on the frequency and treatment time (Cruz‐cansino et al, ). It is suggested that prolonging US treatment time could decrease to a larger extent the microbial load of sonicated samples (Zou & Jiang, ).…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies and reviews have been conducted into the bactericidal effects of ultrasound (US) on an assortment of microorganisms in food produce (Cruz-cansino et al, 2016;Ersus & Turanta, 2013;Gao, Lewis, Ashokkumar, & Hemar, 2013;Piyasena, Mohareb, & Mckellar, 2003). Due to the adverse effects of thermal and chemical washing on the quality of leafy vegetables (Bajpai, Mishra, & Prakash, 2005), physical and non-thermal washing alternatives are been considered including ultrasonic decontamination, especially for fresh agricultural produce (Brilhante São José & Dantas Vanetti, 2012;Freitas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cruz‐Cansino et al () compared pasteurized (70 °C for 30 min) cactus pear juice with thermoultrasonicated (48 °C, 80% amplitude for 15 and 25 min) and observed that 25 min treatment exhibited improved stability regarding color, betalain content, browning index, viscosity, microbial growth, and antioxidant activity during 28 days of storage. In another study, Cruz‐Cansino et al () found that ultrasound treatment at 90% amplitude was most effective in eliminating Escherichia coli inoculated in cactus pear juice and stored for 5 days. An ultrasound amplitude of 100% level for 15 min at 25 °C resulted in significant reduction of Escherichia coli inoculated in pomegranate juice (Alighourchi, Barzegar, Sahari, & Abbasi, ).…”
Section: Introductionmentioning
confidence: 98%
“…The power applied in low frequency (10-1,000 W/cm 2 ) is the technique that involves power US [23]. High power ultrasounds are applied to liquid foods to induce the formation of cavitation bubbles, which cause the breakdown and destruction of microorganism cells [24]. Fig.…”
mentioning
confidence: 99%